ANALISIS KEAKTIFAN BELAJAR SISWA: STUDI KASUS DI SEKOLAH DASAR NEGERI 1 BOLO - Anggun Sofiani; Sri Suryaningsih; Hardyanti Hardyanti (STKIP HARAPAN BIMA, 2024)
This study aims to analyze student learning liveliness at Primary School Negeri 1 Bolo, focusing on aspects of collaboration, engagement, and motivation. The methods employed include questionnaires, observations, and interviews to gather data from 30 fifth-grade students. The results indicate that students exhibit high levels of collaboration and engagement but face challenges in motivation and active participation. These findings suggest the need for implementing more interactive and inclusive teaching strategies to enhance learning liveliness. This research is expected to provide recommendations for educators and school administrators to create a supportive learning environment that fosters students' academic and social development.